Cloud security : techniques and applications - Mohanty, Sachi Nandan; Pothuri, Srikanth; Potluri, Sirisha; Potluri, Sirisha; Potluri; Subba Rao, Katta (Smart Computing Applications, 2021)
This book presents research on the state-of-the-art methods and applications. Security and privacy related issues of cloud are addressed with best practices and approaches for secure cloud computing, such as cloud ontology, blockchain, recommender systems, optimization strategies, data security, intelligent algorithms, defense mechanisms for mitigating DDoS attacks, potential communication algorithms in cloud based IoT, secure cloud solutions.